PEMUNGUTAN PAJAK PADA RESTORAN YANG TIDAK MEMILIKI IZIN MENDIRIKAN BANGUNAN DI KAWASAN KINTAMANI BANGLI - Candrawilasita, Anak Agung Ayu; Parsa, I Wayan; Suardita, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015)
This paper is titled, "Tax Collection At The Restaurant which is Has No Building Permit in Kintamani Bangli Region". The problems discussed in this paper is what the basis used by the Government in the Bangli Regency to collect tax to restaurant that does not have a permit in the area of Kintamani, Bangli and authority of the Government in the Bangli Regency to collect tax to restaurant that does not have a permit in the area of Kintamani, Bangli. The method used is normative juridical research. The basis used by the Government in the Bangli Regency tax purposes to restaurant that does not have a building permit is the principle of expediency. Based the authority that possessed, the Government shall collects tax to restaurant that does not have a permit in the area of Kintamani, Bangli. Conclusion of this paper is the basis used in the conduct of tax collection at the restaurant that does not have a building permit is the principle of expediency. Government in the Bangli Regency can do tax collection at a restaurant that does not have a permit in the area of Kintamani Bangli.
Keywords: Tax Collection, Restaurant Tax, Building Permit, Kintamani